Neural stem cell self-renewal stimulation by store-operated calcium entries in adult mouse area postrema: influence of leptin - Ben Dhaou, Cyrine; Terrié, Elodie; Déliot, Nadine; Harnois, Thomas; Cousin, Laetitia; Arnault, Patricia; Constantin, Bruno; Moyse, Emmanuel; Coronas, Valérie (Frontiers in Cellular Neuroscience, 2023)
Neural stem cells (NSCs) persist in specific brain germinative niches and sustain neurogenesis throughout life in adult mammals. In addition to the two major stem cell niches in the subventricular zone and the hippocampal dentate gyrus, the area postrema located in the brainstem has been identified as a neurogenic zone as well. NSCs are regulated by signals from the microenvironment that adjust stem cell response to the needs of the organism. Evidence accumulated over the past decade indicates that Ca2+ channels play pivotal functions in NSC maintenance. In this study, we explored in area postrema NSCs the presence and roles of a subset of Ca2+ channels, the store-operated Ca2+ channels (SOCs) that have the capacity to transduce extracellular signals into Ca2+ signals. Our data show that NSCs derived from the area postrema express TRPC1 and Orai1, known to form SOCs, as well as their activator STIM1. Ca2+ imaging indicated that NSCs exhibit store-operated Ca2+ entries (SOCEs). Pharmacological blockade of SOCEs with SKF-96365, YM-58483 (also known as BTP2) or GSK-7975A resulted in decreased NSC proliferation and self-renewal, indicating a major role for SOCs in maintaining NSC activity within the area postrema. Furthermore, our results show that leptin, an adipose tissue-derived hormone whose ability to control energy homeostasis is dependent on the area postrema, decreased SOCEs and reduced self-renewal of NSCs in the area postrema. As aberrant SOC function has been linked to an increasing number of diseases, including brain disorders, our study opens new perspectives for NSCs in brain pathophysiology.